Plant-and Animal-Based Protein Sources for Nutritional Boost of Deep-Fried Dough - Mudau, Ndamulelo; Ramavhoya, Khuthadzo; Onipe, Oluwatoyin O.; Jideani, Afam I. O. (Frontiers in Sustainable Food Systems, 2021)
Flaxseed (Linum usitatissimum L.) is an oilseed that is used in both industry and food production. Flaxseed contains biologically active compounds including linolenic acid, linoleic acid, and lignans. Flaxseed powder (2.5 – 10% w/w) and chicken eggs (10 to 30% v/w) were substituted in cake wheat flour for fried dough (magwinya) production. The physicochemical properties of the fried dough were determined and compared with the control. There was a significant (p < 0.05) increase in moisture, protein, ash and hardness and a decrease in fat content of fried dough enriched with egg (FDE) and flaxseed powder (FDFX). Enrichment with 30% (v/w) egg, and/or 7.5 - 10% flaxseed powder resulted in higher protein, oil reduction, and ash contents compared with the rest of the products. With the current interest in plant-based protein, flaxseed is a good choice of flour-based snacks for consumers without compromise in nutrition.